Handicrafts Made from Marine Garbage in East Bintan District, Bintan Regency, Riau Archipelago - Shepia Widianingrum; Safira Nida Risma Latifah; Nikodemus Niko (Formosa Journal of Applied Sciences, 2022)
Crafts made from marine waste are an innovation carried out by craftsmen from East Bintan District, Bintan Regency, Riau Islands. The results of the handicrafts are fish bone boats, flowers from fish scales, flower vases and ornaments made of shells, key chains made of shells and gong gongs, as well as replicas of cherry blossoms made of fish scales. The research method used in this paper is descriptive qualitative. Primary data obtained through field observations and interviews. Meanwhile, secondary data was obtained by utilizing literature sources from online searches. This research contributes to the mapping of handicrafts made from marine debris in the archipelago. In the Bintan Regency area, craftsmen carry out their activities independently. Meanwhile, the support received from the district government, in this case Dekranasda, is in the form of marketing handicrafts at the Dekranasda Bintan gallery. Meanwhile, training regeneration for craftsmen has not been carried out on a massive scale.